Relaxed η-proximal Operator for Solving a Variational-Like Inclusion Problem - Rahaman, Mijanur; Ahmad, Rais; Dilshad, Mohd; Ahmad, Iqbal (Mathematical Modelling and Analysis, 2015)
In this paper, we introduce a new resolvent operator and we call it relaxed η-proximal operator. We demonstrate some of the properties of relaxed η- proximal operator. By applying this concept, we consider and study a variational -like inclusion problem with a nonconvex functional. Based on relaxed η-proximal operator, we define an iterative algorithm to approximate the solutions of a variational-like inclusion problem and the convergence of the iterative sequences generated by the algorithm is also discussed. Our results can be treated as refinement of many previously known results. An example is constructed in support of Theorem 1.